The Translation of Indonesian Proverbs into English Equivalents - Kurniawan, Raju; Rachmawati, Rachmawati; Sartika, Delita (Lingua Cultura, 2024)
The process of translating Indonesian proverbs into their English equivalents reflects complicated interaction between language, culture, and meaning. The objective of the study was to identify the different forms of Indonesian proverbs that have equivalents in the English language, as well as the cultural similarities and differences between Indonesian proverbs and their English equivalents. This study was conducted using qualitative descriptive research methodology and employed document analysis. The data were collected in a form of documents from "Himpunan Lengkap Peribahasa Nusantara, "Kamus Peribahasa, "A Complete Collection of English Proverb, "Proverb from around the World, " and "Oxford Dictionary of Proverb. " From source texts with lexical elements relating to Indonesian culture terms, the researchers obtained another 57 Indonesian proverbs. Once the gathering of data had been carried out, the data was then analyzed through a comparison of Indonesian proverb with its English version. The findings of this study indicate that a number of Indonesian proverbs have equivalents in English with identical meanings. Nevertheless, there are dissimilarities in sentence and proverb classifications, as well as structural forms of proverbs, under the influence of factors such as "history, " "religion, " "values, " "social organization, " and "language. " This project differs from some earlier studies, which tended to focus more on issues of meaning or word-for-word translation. It examines in detail the way cultural elements like history and religious symbols affect the expression of similar ideas in these two different language traditions. This new approach uncovers previously unconsidered patterns in the manifestation of Indonesian collectivist values and English individualist values in proverbs. This helps us make further sense of issues related to intercultural communication and translation studies. One of the recommendations of the researchers is to conduct further research on the use of Indonesian proverbs and their English equivalents by EFL students.